BSL2-compliant lethal mouse model of SARS-CoV-2 and variants of concern to evaluate therapeutics targeting the Spike protein - Manangeeswaran, Mohanraj; Ireland, Derek D. C.; Thacker, Seth G.; Lee, Ha-Na; Kelley-Baker, Logan; Lewkowicz, Aaron P.; Rothlauf, Paul W.; Cornejo Pontelli, Marjorie; Bloyet, Louis-Marie; Eckhaus, Michael A.; Mendoza, Mirian I.; Whelan, Sean; et al. (Frontiers in Immunology, 2022)
Since first reported in 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is rapidly acquiring mutations, particularly in the spike protein, that can modulate pathogenicity, transmission and antibody evasion leading to successive waves of COVID19 infections despite an unprecedented mass vaccination necessitating continuous adaptation of therapeutics. Small animal models can facilitate understanding host-pathogen interactions, target selection for therapeutic drugs, and vaccine development, but availability and cost of studies in BSL3 facilities hinder progress. To generate a BSL2-compatible in vivo system that specifically recapitulates spike protein mediated disease we used replication competent, GFP tagged, recombinant Vesicular Stomatitis Virus where the VSV glycoprotein was replaced by the SARS-CoV-2 spike protein (rVSV-SARS2-S). We show that infection requires hACE2 and challenge of neonatal but not adult, K18-hACE2 transgenic mice (hACE2tg) leads to productive infection of the lungs and brains. Although disease progression was faster in SARS-COV-2 infected mice, infection with both viruses resulted in neuronal infection and encephalitis with increased expression of Interferon-stimulated Irf7, Bst2, Ifi294, as well as CxCL10, CCL5, CLC2, and LILRB4, and both models were uniformly lethal. Further, prophylactic treatment targeting the Spike protein (Receptor Binding Domain) with antibodies resulted in similar levels of protection from lethal infection against rVSV-SARS2-S and SARS-CoV-2 viruses. Strikingly, challenge of neonatal hACE2tg mice with SARS-CoV-2 Variants of Concern (SARS-CoV-2-α, -β, ϒ , or Δ ) or the corresponding rVSV-SARS2-S viruses (rVSV-SARS2-Spike-, rVSV-SARS2-Spike-β, rVSV-SARS2-Spike-ϒ or rVSV-SARS2-Spike-Δ) resulted in increased lethality, suggesting that the Spike protein plays a key role in determining the virulence of each variant. Thus, we propose that rVSV-SARS2-S virus can be used to understand the effect of changes to SARS-CoV-2 spike protein on infection and to evaluate existing or experimental therapeutics targeting spike protein of current or future VOC of SARS-CoV-2 under BSL-2 conditions.